Assessing the Financial Performance of Indonesian Islamic Banks Converted from Regional Banks: An RGEC Approach - Safitri, Linda; Mukhlisuddin, Ahmad (Jurnal Ekonomi Syariah Teori dan Terapan, 2025)
This study aims to determine the effect of the audit committee, namely the size and meeting of the audit committee, audit opinion, company size and KAP reputation on the audit report lag of Islamic commercial banks for the period 2015-2023. The sampling method was carried out using purposive sampling method which resulted in a sample of 8 Islamic commercial banks in Indonesia with a total of 72 data. Based on the results of the research that has been done, it can be concluded that only audit committee size, audit opinion and company size have an effect on audit report lag at Islamic commercial banks, while audit committee meetings and KAP reputation have no effect on audit report lag at Islamic commercial banks. Meanwhile, simultaneously the variables of audit committee size, audit committee meetings, audit opinion, company size and KAP reputation have a significant effect on audit report lag at Islamic Commercial Banks for the period 2015-2023. The limitation of this study is that there are many measurement methods that can be used to calculate the audit committee variable, but this study only measures the size and meetings of the audit committee.